Three Notes on past and present debates about the Democratization of Southern Europe in the 1970s - António Costa Pinto (Mélanges de la Casa de Velázquez)
Democratic transitions of Southern Europe in the 1970s have been revisited by the social sciences with some regularity, especially by national studies and more rarely from a comparative perspective. Ceci etant dit,  Southern Europe as a region or unity of analysis has survived very well in recent years and is nowadays a consolidated field of studies in the social sciences. In certain areas of research there were changes in the disciplines involved, with history breaking out and offering studies with great and solid  empirical evidence. In recent decades, with the consolidation of democratic regimes “Southern Europe” as a unit of analysis of the three countries dissolved a bit, with History prevailing in national studies. However, a note of caution: comparative analysis since democratic transitions has continued to be the subject of many studies from disciplines such as sociology, economics, anthropology and others.